Descemet Membrane Endothelial Keratoplasty as the Gold Standard in Corneal Endothelium Surgery: A Comparative Analysis with Penetrating Keratoplasty and Descemet Stripping Automated Endothelial Keratoplasty - Piasecki, Łukasz; Niemiec, Bartosz; Olesiński, Bruno; Piosik, Szymon; Dudziak, Natalia; Drozd, Zuzanna; Kamińska, Monika; Guzowicz, Zuzanna; Gągałka, Patrycja; Pawłowska, Paulina (Journal of Education, Health and Sport, 2025)
Background. Descemet Membrane Endothelial Keratoplasty (DMEK) represents one of the most advanced surgical techniques in posterior lamellar keratoplasty. This procedure entails the transplantation of donor corneal tissue into a recipient requiring endothelial replacement. The DMEK methodology involves the selective removal of the recipient’s diseased Descemet’s Membrane (DM). Subsequently, the surgeon carefully injects the healthy donor tissue into the anterior chamber. The graft is then unrolled and secured into position using an intrachamber bubble of 20% sulfur hexafluoride (SF6), which facilitates proper graft adhesion. Crucially, the donor tissue consists solely of the DM and the adjacent, functionally intact corneal endothelium. Aim. The objective of this systematic review is to identify and juxtapose the most significant differences among the Descemet Membrane Endothelial Keratoplasty DMEK, DSAEK, and Penetrating Keratoplasty (PK) techniques. Furthermore, a crucial element of this study is to justify the current position of DMEK as the gold standard in the management of corneal endothelial disorders. Material and methods. The materials utilized for this systematic review were retrieved from the PubMed and Google Scholar databases. The following key phrases were employed to search for relevant articles: DMEK, DSAEK, Penetrating Keratoplasty, Endothelial Keratoplasty, and Fuchs Endothelial Dystrophy. All cited works were published no later than 2018. Out of a total of 125 analyzed articles, only 25 containing up-to-date data were ultimately selected and included in this study. Conclusions. The current systematic review confirms that DMEK represents the gold standard for treating endothelial disorders, leading to the gradual abandonment of the higher-risk PK and DSAEK methods. DMEK provides the statistically superior final corrected distance visual acuity and the shortest visual rehabilitation time among the techniques discussed.